Utilization of maternal health care services in a rural community of Nepal (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Nepal has made progress in declining maternal mortality; but not up to the target. One of the important aspects in this regard is to know about the base line maternal health care utilization among women and to develop intervention accordingly. This study aims to identify the utilization of maternal health care services among women of rural municipality of Nepal.Method: A cross sectional analytical study with purposive sampling among 323 married women having at least one child less than five years old was conducted in Bagnaskali rural municipality of Palpa district using face to face interview technique with self-developed structured interview schedule. Descriptive statistics frequency, percentage, mean and standard deviations were used and association between descriptive variables and utilization was done using Chi square and Fisher Exact test as applicable using Statistical Package for Social Sciences (SPSS) version 16.Result: The study showed 21.05% of respondents had completely utilized maternal health care services (four Antenatal Care (ANC) checkups, institutional delivery and three Postnatal Care (PNC) checkups), 78.94% of the respondents had partially utilized services. There was no significant difference in health care utilization between maternal age, education of both mothers and husbands, occupation, types of families and distance to nearest health facility as seen by Chi Square and Fisher Exact Test.Conclusion: Almost all the respondents had ANC checkup and institutional delivery. More than half of the respondents had PNC checkup and the demographic variables had no association with utilization of maternal health care services.